Implementasi Model Problem Based Learning Berpendekatan Saintifik dalam Meningkatkan Kemampuan Pemecahan masalah dan Motivasi Belajar Materi Peluang kelas XII SMA - Sitti Sastriana Bada; Andriyani (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research objective is to improve problem-solving skills and learning motivation with the Problem Based Learning based on the scientific approach to probability material in grade XII. This type of research is classroom action research with two cycles, with each cycle containing four stages: planning, implementation, observation, and reflection. The data collection used a problem-solving ability test and a learning motivation questionnaire. The research sample is students of grade XII MIA 1 SMA Negeri 1 Tikep. From the research results in the first cycle, the average value of problem-solving abilities increased by 8.22, from 58.21 to 66.43. Then continued improvement in cycle II, with the average value of problem-solving ability increased by 16.97, from 65.71 to 82.68. While the learning motivation questionnaire results show an improvement in students' average response of 28%, from 59% to 87%. Based on the research, it can be concluded that the Problem Based Learning model can improve problem-solving abilities and student motivation.